Presence of the Andean Bear’s (Tremarctos ornatus) new evidences in the Yungas of Puno, Peru’s southernmost record - Márquez, Gisella (2010)
The Spectacled bear (Tremarctos ornatus) is the only representative of the family Ursidae in South America. The largest and most continuous Andean bear population in Peru is located on the eastern slopes of the Ori- ental Range, including Departamento Puno, where most reports are based only on surveys. We describe two indirect records of Andean bear’s presence from Departamento Puno, obtained on August 2009. The first record is a scat with seeds belonging to the family Lauraceae, and found in Yanacocha; the second record consists of some bear's claw marks found in Challohuma, which represents also the southernmost confirmed record of the Spectacled bear in Peru. Also our records confirm a continuous distribution of this species on the eastern Andean slopes from southern Peru to northwestern Bolivia. Furthermore, these records, found very close to the highly diverse Bahuaja Sonene National Park (BSNP), suggest it is very important to establish conservation strategies both within and outside of BSNP’s buffer zone.